Identification of prehistoric malting and partial grain germination from starch granules in charred barley grains. (January 2021) - Cordes, Adam; Henriksen, Peter Steen; Hald, Mette Marie; Sørensen, Lasse; Nielsen, Poul Otto; Xu, Jinchuan; Lund, Jørgen; Møller, Niels Algreen; Nielsen, Finn Ole Sonne; Sarauw, Torben; Simonsen, John; Sparrevohn, Lotte Reedtz; et al.
Abstract: This paper presents results from a study of starch granules in charred archaeological grains with the purpose of identifying markers of malting. Starch granules are microstructures from plant organs that can be identified to the level of plant genus based on their shape and size. Starch granules have been extracted from archaeological deposits. However, surprisingly few studies have focused on identifying starch granules preserved in the actual cereal grains. This study included experimental charring of modern cereal grains to investigate whether starch granules survive charring, as well as investigating an assemblage of charred barley grains from Danish archaeological excavations spanning the Early Neolithic (3900 BCE) to the Late Viking Age (1050 CE). We show that starch granule structures can be preserved in charred archaeological grains using Scanning Electron Microscopy (SEM). Three different types/phases of starch granule preservation in charred archaeological grains are observed: 1) separate granules, 2) partly plastisized granules and 3) fully plastisized granules. Two grains dated to the Viking Age (800 CE – 1050 CE) and 1st century CE (Roman Iron Age), respectively, had holes on the surface of their starch granule similar to those seen in malted/germinated barley (called amylolytic pores). Both grains were found in circumstances with other indications of malting activity. Another grain dated to 50 BCE (Pre-Roman Iron Age) also contained starch granules with amylolytic pores that marks the beginning of germination. However, this grain was found in a vessel of stored unthreshed grain in a grain storage basement and therefore is more likely to be an outcome of unintended germination. The identification of the germination process – accidental or deliberate – from starch granules in charred cereal grains means that we are now able to identify malting in prehistory from the cereal grains themselves, including naked grains, which has hitherto not been possible on morphological grounds. Highlights: SEM shows partial preservation of cell structures in charred archaeological grains. Starch granules are occasionally preserved in charred grains from Danish prehistory. Different phases of starch granule plasticization can be distinguished. Signs of malting can be seen in charred archaeological cereal grains. Wet harvest and/or storage conditions may leave marks on the starch granules.